The effect of ischemic preconditioning on performance and recovery during repeated supramaximal cycling bouts - Smith. L. E.; Van Guilder. G. P.; Buchanan, C. A.; Dalleck, L. C. (Outside, 2019)
Introduction: Ischemic preconditioning (IPC), a process of cyclically occluding and reperfusing blood to tissue, has been shown to preserve ATP, prolong vasodilation, and enhance exercise performance. Purpose: The aim of this study was to test the effects of IPC on repeated supramaximal cycling performance and recovery in 12 experienced cyclists. Methods: In a randomized, double-blind, placebo controlled, cross-over design, subjects received a 4 x 5 min bilateral leg IPC treatment then performed a supramaximal cycling trial, followed by a 20 min passive recovery, then repeated the identical trial and recovery again. Time to fatigue (TTF) for each trial was measured as well as blood lactate (La-) and pH at minute 0, 5, 10, 15, and 20 during the passive recovery. Results: No significant effect was found for IPC on TTF for trial A (p>.05) and trial B (p>.05), however a great amount of individual variability was observed. No significant effect was found for IPC on the amount of La- and pH recovery for trial A (p>.05) and B (p>.05). A significant effect was found earlier on the rate of La- recovery in the IPC condition compared to placebo in both trial A (p<.05) and trial B (p<.05). Conclusion: These results suggest there is no effect of IPC on repeated supramaximal cycling performance, nor the amount of blood lactate or pH recovery, however, IPC does have an effect on the rate of blood lactate recovery.